Awareness of hibah among staff in Pejabat Agama Islam Daerah (PAID) Baling - Azman, Norshahira (2025)
The study focusses at the understanding, acceptance, and acceptability of hibah as an estate planning tool among the staff of Pejabat Agama Daerah (PAID) Baling. Hibah, an Islamic legal term that refers to the voluntary transfer of property ownership, holds great potential for settling inheritance disputes and encouraging transparent wealth distribution in accordance with Islamic norms. The study reveals a large knowledge and awareness gap about hibah among PAID personnel, which has an impact on its execution and perceived advantages. The study employed a quantitative technique, with questionnaires delivered to 108 respondents to analyze their demographic characteristics and attitudes towards hibah. Key findings show that, while most respondents recognize the value of hibah as a property planning tool, knowledge of its legal and procedural components is limited. Factors such as education level and exposure to organized information impact respondents' understanding and acceptance of hibah. The study emphasizes the need for focused educational programs to raise knowledge and dispel myths regarding hibah, notably its conformity with Islamic inheritance regulations such as faraid. Furthermore, the findings highlight legal and procedural differences, emphasizing the importance of a uniform legal framework and greater regulatory control to prevent abuse and fraud. By addressing these gaps via joint efforts including religious authorities, legal professionals, and financial institutions, hibah can be better used as a tool for equitable and transparent estate planning. This study adds vital insights to Islamic financial studies and lays the groundwork for further investigation of hibah's uses.